Method Modification to Extend the Matrix Claim of the Thermo Scientific RapidFinder Salmonella species, Typhimurium, and Enteritidis Multiplex PCR Kit. (23rd November 2019) - Williams, Jessica; Evans, Katharine; Crabtree, David; Hughes, Annette; Cooper, Charlotte; Rose, Helen; Kauppinen, Mikko; Flannery, Jonathan; Meibers, Hannah; Bird, Patrick; Benzinger, M Joseph; Agin, James; et al.
Abstract: Background : The Thermo Scientific RapidFinder™ Salmonella species, Typhimurium and Enteritidis Multiplex PCR Kit is a real-time multiplex PCR assay for the detection and differentiation of Salmonella species, Salmonella Typhimurium, and S. Enteritidis from poultry, pork, and environmental samples. The method has previously been granted certification as Performance Tested Method SM (PTM) 081701, validated according to the AOAC Research Institute (RI) PTM program for poultry (chicken thighs with skin, chicken wings with skin, and chicken nuggets), raw pork sausage matrixes, and stainless steel environmental surface sponges. Objective : This report details the method modification study to validate ground turkey (375 g sample size), chicken carcass rinse, and shell egg matrixes. Methods : The candidate method was compared with the U.S. Food and Drug Administration's Bacteriological Analytical Manual Chapter 5 for shell eggs and the U.S. Department of Agriculture Food Safety and Inspection Service's Microbiology Laboratory Guidebook 4.09 for ground turkey (375 g) and chicken carcass rinse matrixes. Results : The statistically significant differences found between the candidate and reference methods upon analysis by probability of detection were in favor of the candidate method. Inclusivity and exclusivity testing demonstrated that the RapidFinder Salmonella species, Typhimurium and Enteritidis Multiplex PCR Kit was able to detect all the major groups of Salmonella . All exclusivity isolates were correctly excluded. Conclusions : The data presented in this report show that the candidate is suitable for the detection and differentiation of Salmonellae from shell egg, chicken carcass rinse, and ground turkey (375 g) matrixes. Highlights: Thermo Scientific RapidFinder Salmonella species, Typhimurium and Enteritidis Multiplex PCR Kit (candidate method) matrix claims extended to include ground turkey (375 g), chicken carcass rinse and shell egg samples.